DIFFICULTY IN THE EARLY DIAGNOSIS OF AUTISTIC SPECTRUM DISORDERS AND THEIR FAMILY IMPACT (CIPEEX, 2022)
AUTISM SPECTRUM DISORDER (ASD) IS A SYNDROME THAT CAUSES DIFFICULTIES IN COMMUNICATION, IMAGINATION AND SOCIAL INTERACTION. THUS, ITS DIAGNOSIS IS PERFORMED ONLY BY CLINICAL EVALUATIONS AND THERE IS NO PROVEN LABORATORY TEST THAT ASSISTS IN THE EARLY DIAGNOSIS OF THE DISEASE. THEREFORE, THERE ARE SEVERAL COMPLICATIONS FOR THE INVESTIGATION OF THIS DISEASE, SUCH AS THE VARIABILITY OF THE PRESENTATION OF THE SYMPTOMS, THE SHORTAGE OF PROFESSIONALS QUALIFIED TO RECOGNIZE THE CHANGES AND THE LACK OF SPECIALIZED SERVICES. ADDED TO THIS, AUTISM IS A COMMON SUBJECT, BUT LITTLE CLARIFIED IN THE SOCIAL SCOPE, SO WHEN A CHILD PRESENTS THE FIRST SIGNS THE PARENTS FIND THEMSELVES LAY AND OTHERS AND, OFTEN, THEY BELIEVE THAT IT IS ONLY A CHARACTERISTIC OF THE CHILD. IN THIS WAY, THE DIAGNOSIS IS MADE LATE AND CAUSES SEVERAL IMPACTS IN THE FAMILY ROUTINE, CAUSING A REVERSAL OF ROLES, WITH THE MOTHER WITH THE FOCUS TOTALLY DIRECTED TO THE AUTISTIC CHILD AND THE FATHER TO THE FINANCIAL ONE. SUCH BEHAVIOR CAUSES OVERPROTECTION OF FAMILY MEMBERS, CAUSING SIBLINGS JEALOUSY AND TOO MUCH OVERLOAD ON THE MOTHER. THUS, THROUGH AN INTEGRATIVE REVIEW, THE OBJECTIVE OF THIS WORK IS TO ADDRESS THE DIFFICULTIES OF EARLY DIAGNOSIS OF PEOPLE WITH AUTISM AND THEIR IMPACT WITHIN THE FAMILY. WE USED AN INTEGRATIVE REVIEW OF THE LITERATURE, SELECTING 28 ARTICLES THAT PRESENTED CHARACTERISTICS THAT BEST ANSWERED THE QUESTION: WHAT ARE THE DIFFICULTIES FOR THE DIAGNOSIS OF ASD AND ITS RELATION TO FAMILY INTERACTION? IN THE FACE OF THE ANALYZED, IT WAS CONCLUDED THAT TO THE DETRIMENT OF THE SCARCITY OF LABORATORY TESTS AND THE SUBJECTIVITY OF THE SYMPTOMS, THE DIAGNOSIS OF THIS DISEASE OCCURS LATE AND CAUSES GREAT FAMILY IMPACT. IN VIEW OF THIS, MORE SCIENTIFIC AND MEDICAL RESEARCH IS NEEDED REGARDING THE ETIOLOGY AND FACTORS THAT DETERMINE THE SYNDROME, AS WELL AS A MULTIPROFESSIONAL TEAM THAT SUPPORTS THE CHILD AND THE FAMILY.
Keywords: Autism. Diagnosis. Dificulty. Autism Spectrum Disorder.